2017
DOI: 10.1186/s12876-017-0581-1
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of Life in patients with chronic hepatitis C receiving Sofosbuvir-based treatment, with and without Interferon: a prospective observational study in Egypt

Abstract: BackgroundThe Egyptian government introduced the first directly acting antivirals (DAAs) into Egypt through the government funded National Treatment Program. As yet, there has been no investigation into the effects of these new DAAs therapies on patient reported outcomes (PROs). This study aimed to (1) assess the PROs (health-related quality of life (HRQoL), mental health and perceived social support) of HCV patients receiving DAAs therapy prior, during and at the end of therapy; (2) evaluate PROs of Interfero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 42 publications
1
18
1
1
Order By: Relevance
“…Two possible shortcomings of our study need to be considered. First, the population size, although similar or greater than that of other observational studies [ 35 , 14 , 57 ] was not large enough to obtain conclusive results in some subanalyses. In any case, the patients included accounted for 78% of the patients who received treatment successfully during the study period.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Two possible shortcomings of our study need to be considered. First, the population size, although similar or greater than that of other observational studies [ 35 , 14 , 57 ] was not large enough to obtain conclusive results in some subanalyses. In any case, the patients included accounted for 78% of the patients who received treatment successfully during the study period.…”
Section: Discussionmentioning
confidence: 88%
“…Middle age, baseline anxiety-depression, advanced fibrosis and cirrhosis were found to be the most consistent predictors of HRQoL improvements after SVR. Precisely, those factors have been previously associated with impairment in HRQoL among chronic hepatitis C patients [ 4 , 29 , 48 ] and appear to be key determinants for HRQoL deterioration prior to therapy [ 14 ]. The high prevalence of depression and anxiety in HCV patients before treatment initiation [ 49 ] would reinforce the need for psychosocial screening, even more when considering that a greater HRQoL improvement may occurs in those patients after SVR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The actual causes of cirrhosis of liver can't be identified yet [14]. However, most of the studies reported that chronic hepatitis B and hepatitis C infection are the causes of more than half of all cases of liver cirrhosis [1] [2] [4] [15]- [20].…”
Section: Introductionmentioning
confidence: 99%
“…Thereby reducing HRQOL during treatment (12,13). On the other hand, IFN-free DAAs have been reported to have little impact on HRQOL and side effects during treatment (14)(15)(16)(17) The purpose of this study was to evaluate HRQOL on the clinical course of patients with chronic hepatitis C (CHC) receiving DCV/ASV therapy using the Short Form-36 (SF-36) and comparison between younger (<70) and elderly (≥70) patients.…”
Section: Introductionmentioning
confidence: 99%